2021
DOI: 10.18778/1508-2008.24.27
|View full text |Cite
|
Sign up to set email alerts
|

Inequality and Students’ PISA 2018 Performance: a Cross-Country Study

Abstract: The aim of this paper was to investigate the relationship between countries’ PISA study results from 2018 and a set of indices related to socio-economic inequality, such as the Gini index, human development index, or gender inequality index, along with purely economic variables, such as GDP per capita and government expenditure on education. The study covered 70 countries, consisting of 37 OECD countries and 33 non-OECD countries. Research methods included multivariate linear regression models, k-means cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Moreover, some researchers also revealed that countries with more developed economy and advanced educational system show more enthusiasm for ILSA (Robitaille & Garden, 1989cited in Wagemaker, 2020. In addition, there is a significant correlation between student academic achievement and economic growth of the country (Hanushek &Woessmann, 2011 cited in Mazurek, García andRico, 2021). These factors may contribute to the difficulty for developing countries to keep pace with developed countries.…”
Section: Previous Literature On Ilsa and Education Inequalitiesmentioning
confidence: 99%
“…Moreover, some researchers also revealed that countries with more developed economy and advanced educational system show more enthusiasm for ILSA (Robitaille & Garden, 1989cited in Wagemaker, 2020. In addition, there is a significant correlation between student academic achievement and economic growth of the country (Hanushek &Woessmann, 2011 cited in Mazurek, García andRico, 2021). These factors may contribute to the difficulty for developing countries to keep pace with developed countries.…”
Section: Previous Literature On Ilsa and Education Inequalitiesmentioning
confidence: 99%